The influence of cultural factors on the collapse of the Greenland Norse civilization - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2008)
The understanding of the collapse of ancient civilizations is important for the understanding of very complex process happening in our civilization. The Earth is put in danger due to many reasons and some of them do not change throughout history. Because of the global range of human actions, the power reached by contemporary man is much more dangerous than it used to be centuries ago. Therefore, the understanding of the past collapses is crucial for the safety of our global village. The article shows the reasons for the collapse of the Greenland Norse civilization. It seems that the main reason was climate change but it also seems that the Greenland Norse could have survived, or at least postponed the collapse. The author indicates that cultural factors were the roots of ecological degradation and the lack of economic adaptation. The Norse knew the Inuit and their adaptive strategies but did not learn from them. It seems that the collapse of the Greenland Norse civilization was the choice of the Norse’s elite. The leaders kept the society in a risky balance in order to rule over them, but finally, the fragile equilibrium was shattered and caused the collapse.